Development of entrepreneurship literacy education model, pioneering of business incubators oriented food security in rural communities of Yogyakarta special region - Serafin Wisni Septiarti; Nur Djazifah Endang Rosjdijati; RB Suharta (JOURNAL OF EDUCATION, 2014)
This research aims to describe the development of an entrepreneurship literacy education model, the pioneering effort of business incubator   oriented to food security. Two of  the 83 locations as food insecure areas in all of Yogyakarta Special Province, were chosen as research locations. These two locations are Nglipar at Gunungkidul district  and Lendah at Kulonprogo district. Beside that, in the two locations was built Community Learning Center (CLC) to perform the private literacy which became the literacy education model oriented to food security. The data were collected through focus group discussion (FDG), observation, profound interview and documentation. The result indicated that the development of the private business literacy model with the CLC  as the facilitator could be developed through the education and training process. (a) For the two areas with the food insecurity, this development model means that group granary organization became a dynamic agent of literacy education program oriented to sustainability, integrating, and diversification which could motivate the community as a generator of social economic change. (b) the pioneer of group granary with gabah (unhulled paddy separated from the stalks) as a medium revitalized the ongoing formation group, togetherness, and saving or investing movement. (c) it became a group movement in anticipating the food insecurity such as lack of food situation, drought caused by long dry season